2008
DOI: 10.1021/ef800530p
|View full text |Cite
|
Sign up to set email alerts
|

Branching Structure of Diesel and Lubricant Base Oils Prepared by Isomerization/Hydrocracking of Fischer−Tropsch Waxes and α-Olefins

Abstract: Lubricant base oils were prepared from two Fischer-Tropsch (FT) waxes and two R-olefins with different carbon number distributions under several isomerization/hydrocracking conditions. The molecular structures of the resulting oils were investigated using 13 C NMR analysis to determine the location and length of branches. Peak areas assigned to the CH carbons were divided into eight groups and correlated with the progress of the isomerization reaction. Each group showed good correlation with the density of bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 18 publications
(47 reference statements)
0
13
0
Order By: Relevance
“…4) Lubricating base oils can be prepared from Fischer-Tropsch waxes by hydroisomerization to improve the cold-flow properties of the otherwise solid material [105,106]. With longer chain feed materials, there is always the risk of cracking, which is why mildly acidic catalysts perform so much better for the hydroisomerization of heavier n-alkane feed materials than their more acidic counterparts.…”
Section: Hydroisomerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…4) Lubricating base oils can be prepared from Fischer-Tropsch waxes by hydroisomerization to improve the cold-flow properties of the otherwise solid material [105,106]. With longer chain feed materials, there is always the risk of cracking, which is why mildly acidic catalysts perform so much better for the hydroisomerization of heavier n-alkane feed materials than their more acidic counterparts.…”
Section: Hydroisomerizationmentioning
confidence: 99%
“…Lubricant base oils can be produced from LTFT syncrude [105,106], as well as from HTFT syncrude [114]. 2) Production of distillate from C 23 and heavier material.…”
Section: Hydrocrackingmentioning
confidence: 99%
“…Nevertheless, a number of investigations have been reported that studied LTFT wax HCR over the metal-promoted zeolites USY, Beta and mordenite. 429,463,464 There is also the possibility that in the future zeolite catalysts may be developed to exploit the 'window effect' for hydrocracking of Fischer-Tropsch waxes. 465 The 'window effect' was reported for HCR over ERI zeolite catalysts, which yielded a bimodal product distribution with maxima at C 3 -C 4 and C 10 -C 12 , but few products in the C 5 -C 8 range.…”
Section: Bifunctional Zeolitic Silica-alumina Hcr Catalystsmentioning
confidence: 99%
“…Kobayashi and co-workers used a 13 C NMR method to investigate the molecular structures of the lube base oil and diesel fuel that can be prepared from Fischer-Tropsch waxes by HIS/HCR. [45][46][47] The aim was to determine the location and length of the branches. It was observed that the probability of methyl branching on the main carbon chain decreased in the order 2nd43rd44th and so on; the probability of methyl branching on the seventh, eighth and inner carbon atoms was almost equal.…”
Section: Hydroisomerisation Of Waxesmentioning
confidence: 99%